1998
DOI: 10.1111/j.1572-0241.1998.445_o.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endoscopic Variceal Ligation on Oxygen Transport and the Arterial Lactate Levels in Patients With Cirrhosis

Abstract: We found a significant decrease in the oxygen delivery in patients undergoing an endoscopic variceal ligation. Such deteriorated tissue oxygenation may be serious especially in patients with a low oxygen transport ability such as in patients with variceal hemorrhage with anemia. However, the clinical significance of these changes remains unclear and further studies are therefore warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As early as 1996, reports emerged highlighting a related phenomenon wherein EVL surgery may exacerbate liver tissue ischemia and hypoxia. This study observed a decrease in cardiac output and oxygen delivery immediately after EVL surgery, although the underlying causes and implications were not fully understood at the time [18] . This hypoxic condition is particularly pronounced in patients with varicose veins and anemia.…”
Section: Discussionmentioning
confidence: 81%
“…As early as 1996, reports emerged highlighting a related phenomenon wherein EVL surgery may exacerbate liver tissue ischemia and hypoxia. This study observed a decrease in cardiac output and oxygen delivery immediately after EVL surgery, although the underlying causes and implications were not fully understood at the time [18] . This hypoxic condition is particularly pronounced in patients with varicose veins and anemia.…”
Section: Discussionmentioning
confidence: 81%